Origin of the right pulmonary artery from the ascending aorta. - Fontana, G P (1987)
Origin of the right pulmonary artery from the aorta is a congenital malformation usually associated with serious symptoms in the first year of life and characterized by a poor prognosis. Sixty-five patients with this disorder have been reviewed in the literature, and 95% presented during the first year with signs of congestive heart failure. All had cardiomegaly by radiographic and electrocardiographic examination. An accurate diagnosis was established by cineangiography, and associated cardiovascular anomalies were present in 85%. Origin of the right pulmonary artery from the ascending aorta is much more common than origin of the left pulmonary artery from this vessel (8 to 1). Twenty-three patients were managed without operation with a 30% 1-year survival rate. Among those patients managed surgically, the survival rate was 84% at 1 year. It is now clear that operation should be done as early as possible to prevent irreversible changes occurring in the pulmonary arterial vasculature since microscopic features of pulmonary hypertension have been seen during the first month of life. One patient was operated on at 5 months with correction of the deformity. The pulmonary arterial pressure decreased to normal after operation. This child is now asymptomatic and his 10-year postoperative follow-up is the longest found in the literature.